Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2017)
A dataset containing 1550 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Cynara cardunculus subsp. flavescens Wiklund", "HasGeospatialIssue is false", "HasCoordinate is true" ] } The dataset includes 1550 records from 11 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0082627-160910150852091/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences